Inovasi Penilaian Otentik Maharah Kalam dengan Pendekatan Komunikatif pada Buku Bahasa Arab MI Kelas III - Yuristira, Afif Naufal Andrean; Baroroh, Umi; Purnama, Boby Bagas; Kirani, Lintang Lutfhi; Hardiyanti, Iin (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2025)
Assessment is an integral part of the language learning process, including in the teaching of Arabic at Madrasah Ibtidaiyah (MI/Islamic elementary schools). One of the main skills to be developed is maharah kalam (speaking skill), which requires students to actively and communicatively use the Arabic language. This study aims to examine the speaking assessment techniques found in the Arabic Language Textbook for Grade III MI published by the Indonesian Ministry of Religious Affairs in 2020, and to propose an innovation through authentic assessment using a communicative approach that is more contextual and meaningful. This research employs a library research method with content and descriptive analysis techniques. The findings indicate that the assessment techniques in the textbook remain conventional, focusing on vocabulary pronunciation, dialogue repetition, and simple oral responses. These techniques do not fully reflect the real-life communicative use of language. Therefore, there is a need for authentic assessment innovations based on a communicative approach through activities such as role-playing, interviews, discussions, and oral presentations. Such innovations can provide a more comprehensive overview of students' competencies—cognitive, affective, and psychomotor—and support the goal of Arabic language instruction as an active communication tool.